2017
DOI: 10.1016/j.drugpo.2017.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare contact and treatment uptake following hepatitis C virus screening and counseling among rural Appalachian people who use drugs

Abstract: Background Hepatitis C virus (HCV) remains a major contributor to morbidity and mortality worldwide. Since 2009, Kentucky has led the United States in cases of acute HCV, driven largely by injection drug use in rural areas. Improved treatment regimens hold promise of mitigating the impact and transmission of HCV, but numerous barriers obstruct people who inject drugs (PWID) from receiving care, particularly in medically underserved settings. Methods 503 rural people who use drugs were recruited using respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…Morbidity and mortality related to chronic HCV infection continues to increase, driven by large populations of people living with HCV who acquired the infection decades ago. While potentially curative treatment for HCV infection has been available for over 15 years, these medications were poorly tolerated and had low cure rates, resulting in fewer than 15% of those infected being treated. HCV cure is associated with reduced morbidity and mortality, but low treatment uptake and poor efficacy with older medications limited population‐level effects.…”
Section: Introductionmentioning
confidence: 99%
“…Morbidity and mortality related to chronic HCV infection continues to increase, driven by large populations of people living with HCV who acquired the infection decades ago. While potentially curative treatment for HCV infection has been available for over 15 years, these medications were poorly tolerated and had low cure rates, resulting in fewer than 15% of those infected being treated. HCV cure is associated with reduced morbidity and mortality, but low treatment uptake and poor efficacy with older medications limited population‐level effects.…”
Section: Introductionmentioning
confidence: 99%
“…(Alam-Mehrjerdi et al, 2016;Mah et al, 2017;Zeremski et al, 2014) Hepatitis C education campaigns can improve knowledge, (Norton et al, 2014;Surjadi et al, 2011) and a formal hepatitis C education program can shorten time to treatment and improve virologic response. (Lubega, Agbim, Surjadi, Mahoney, & Khalili, 2013) In a screening program focused on people who use drugs in rural Appalachia, a portion of which includes Virginia, only 8% received treatment after testing positive for hepatitis C, (Stephens, Young, & Havens, 2017) demonstrating a significant need for improvement in linkage to care and treatment. Given the limited knowledge within our cohort, there is room for improvement through educational campaigns.…”
Section: Discussionmentioning
confidence: 99%
“…4 , 5 A recent study has demonstrated a need for further HCV testing and intervention in the Appalachian region. 6 Among Central Appalachia states, West Virginia currently has the second-highest incident rate of HCV in the nation. 4 Of particular concern is the fact that HCV co-infection has been observed in rates as high as 90% among human immunodeficiency virus (HIV) positive injection drug users.…”
Section: Introductionmentioning
confidence: 99%